Peripheral and Central Mechanisms of Persistent Orofacial Pain - Shinoda, Masamichi; Kubo, Asako; Hayashi, Yoshinori; Iwata, Koichi (Frontiers in Neuroscience, 2019)
Neuroplastic changes in the neuronal networks involving the trigeminal ganglion (TG), trigeminal spinal subnucleus caudalis (Vc), and upper cervical spinal cord (C1/C2) are considered the mechanisms underlying the ectopic orofacial hypersensitivity associated with trigeminal nerve injury or orofacial inflammation. It has been reported that peripheral nerve injury causes injury discharges in the TG neurons, and a barrage of action potentials is generated in TG neurons and conveyed to the Vc and C1/C2 after trigeminal nerve injury. Long after trigeminal nerve injury, various molecules are produced in the TG neurons, and these molecules are released from the soma of TG neurons and are transported to the central and peripheral terminals of TG neurons. These changes within the TG cause neuroplastic changes in TG neurons and they become sensitized. Thline neuronal activity of TG neurons is further accelerated, and Vc and C1/C2 neurons are also sensitized. In addition to this cascade, non-neuronal glial cells are also involved in the enhancement of the neuronal activity of TG, Vc, and C1/C2 neurons. Satellite glial cells and macrophages are activated in the TG after trigeminal nerve injury and orofacial inflammation. Microglial cells and astrocytes are also activated in the Vc and C1/C2 regions. It is considered that functional interaction between non-neuronal cells and neurons in the TG, Vc, and C1/C2 regions is a key mechanism involved in the enhancement of neuronal excitability after nerve injury or inflammation. In this article, the detailed mechanisms underlying ectopic orofacial hyperalgesia associated with trigeminal nerve injury and orofacial inflammation are addressed.